The Effect Of Oxytosin Massage Through The Back On The Production Of Breast Milk In Post Partum Mother In The Mother Of Permata Bunda Subdistrict Babat - dwi kurnia purnama sari (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2019)
Every minute of one baby indonesia died because they did not to obtain breast milk (BM) in the first hour of birth, problems in the provision of breastfeeding can because production breastfeeding not out.One way to overcome the incomplete milk production is by doing a massage of oxytocin through the back. This message can relax the mother’s so that stimulate oxcytocin reflex and milk production also smoothly. The purpose of this research to know the influence of massage oxytocin through the back to production breastfeeding on the post partum. This research using design Quasy experimental that involves 30 respondents taken with systematic random sampling. Respondents divided into 2 groups, namely the control group were 15 respondents and group experimental were 15 respondents.Data collection use observation checklist.Data analyzed using chi-square test with a significant degree α ≤ 0.05. The results of statistical tests chi square obtained p value = 0,028 (α< 0,05)thus H1 accepted that mean there are influence massage oxytocin through the back to production breastfeeding on the post partum. The research at the clinic Permata BundaSubdistrict Babat that is the massage oxytocin through the back to production breastfeeding. Because massage oxytocin through the back can stimulate reflexes oxytocin hormone. Expected for health workers can provide health education about massage oxytocin through the back to the community so later expected all the community be able to apply massage oxytocin through the back to overcome it swift sailboat production breastfeeding.